2021
DOI: 10.3390/genes12111834
|View full text |Cite
|
Sign up to set email alerts
|

DRD4 Exon 3 Gene Polymorphisms in Patients Diagnosed with Polysubstance Use Disorder and Co-Occurrence of a Depressive Episode

Abstract: Background: There has been a noticeable and systematic growth of the use of psychoactive substances over the past few decades. Dual diagnosis is a clinical term referring to the occurrence of psychoactive substance use disorder comorbid with another psychiatric disorder in the same person. The most common type of dual diagnosis is the co-occurrence of alcohol use disorder and mood disorders in the form of a depressive episode. Co-occurrent substance use disorders are frequently influenced by genetic factors. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Other research studies showed that the combination of two highly prevalent DRD2 SNPs, rs6276 and rs6277, decreased the expression of DRD2 as a consequence of a diminished DRD2 mRNA, and moreover, a decreased D2R receptor availability and affinity [ 70 , 72 , 162 , 163 , 164 , 165 ]. Han et al found that these combined effects of DRD2 and SNPs also diminished the levels of phosphorylated β-catenin, presumably causing more β-catenin to be successfully degraded, and in this way, the transcription of the Wnt/β-catenin pathway of the target genes was stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…Other research studies showed that the combination of two highly prevalent DRD2 SNPs, rs6276 and rs6277, decreased the expression of DRD2 as a consequence of a diminished DRD2 mRNA, and moreover, a decreased D2R receptor availability and affinity [ 70 , 72 , 162 , 163 , 164 , 165 ]. Han et al found that these combined effects of DRD2 and SNPs also diminished the levels of phosphorylated β-catenin, presumably causing more β-catenin to be successfully degraded, and in this way, the transcription of the Wnt/β-catenin pathway of the target genes was stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…The main findings of our study are that interactions between DAT1 polymorphism, neuroticism, and NPS use were found. Neuroticism is a personality dimension that involves emotional reactivity [ 36 , 37 , 38 , 39 ]. Individuals whose scores are high for neuroticism are more sensitive to negative mood states and have excessive vulnerability to environmental stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the DAT1 gene and the personality traits measured using the TPQ test was also performed by Tzeng and colleagues [ 36 ] on a large cohort of Chinese male subjects diagnosed with amphetamine use disorder. Novelty seeking and harm avoidance scores were higher in the case group than in the controls, but the analyzed polymorphism did not influence the scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation